Does pre-exercise stretching affect muscle tendon unit compliance? - McGuigan, M. P.; Farris, D. J.; Wood, M. J.; Abbas, A.; Trewartha, G. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Pre-exercise stretching is carried out by the majority of recreational and professional athletes, yet there is conflicting evidence with regard to the benefits of such programmes to either performance or injury risk reduction. It is unclear whether pre-exercise stretching can affect compliance, and at what level of the muscle-tendon unit (MTU) this effect may occur. Therefore the aim of this study was to determine whether an active preexercise stretching protocol increased the compliance of the triceps surae muscle-tendon complex and whether changes in compliance occurred in the muscle body or free tendon. This study has identified that pre-exercise stretching does not significantly increase the compliance of the Achilles tendon, but does increase the compliance of the muscle body. This suggests that pre-exercise stretching may alter the strain characteristics of the muscle fascicles without affecting the force transmission through the tendon. This has implications for both athletic performance and injury prevention.